Introduction to Logic
Assume a language with object constant a and unary function constants f and g. Given p(a), ∀x.(p(x) ⇒ p(f(x))), and ∀x.(p(f(x)) ⇒ p(g(x))), use the Fitch system with Tree Induction to prove ∀x.p(x).
Show Instructions
To apply a rule of inference, check the lines you wish to use as premises and click the button for the rule of inference. Reiteration allows you to repeat an earlier item. To delete one or more lines from a proof, check the desired lines and click Delete. When entering expressions, use Ascii characters only. Use ~ for ¬; use & for ∧; use  for ∨; use => for ⇒; use <=> for ⇔; use A for ∀; use E for ∃; and use : for . in quantified sentences. Also, for variables use strings of alphanumeric characters that begin with a capital letter. For example, to write the sentence ∀x.∃y.(p(x) ∧ q(y) ⇒ r(y)∨¬s(y)), write AX:EY:(p(X)&q(Y)=>r(Y)~s(Y)).
1
p(a)
Premise
2
AX:(p(X) => p(f(X)))
Premise
3
AX:(p(f(X)) => p(g(X)))
Premise
4
p(X)
Assumption
5
p(X) => p(f(X))
Universal Elimination
2
6
p(f(X))
Implication Elimination
5
4
7
p(f(X)) => p(g(X))
Universal Elimination
3
8
p(g(X))
Implication Elimination
7
6
9
p(X) => p(g(X))
Implication Introduction
4
8
10
AX:(p(X) => p(g(X)))
Universal Introduction
9
11
AX:p(X)
Induction
1
2
10
